Optimization Method and Stability Test to Determinate Luteolin, Quercetin, Apigenin, and Sinensetin Levels in Herbal Medicines Using TLC-Densitometry - Muhammad Hidayatullah; Mochammad Yuwono; Riesta Primaharinastiti (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Nephrolithiasis is a condition in which there are one or more kidney stones in the pelvis or calyces. Luteolin, quercetin, apigenin, and sinensetin are marker compounds in the extracts of Plantago major, Sonchus arvensis, Strobilanthes crispus and Orthosiphon stamineus which have nephrolithiasis activity. To control the quality of herbal medicines, a TLC-Densitometry method was developed in this study using luteolin, quercetin, apigenin, and sinensetin as phytochemical markers. Objective: The present work aimed to develop optimal conditions for analyzing luteolin, quercetin, apigenin, and sinensetin. Methods: Determination of optimal conditions for analysis is carried out by determining the composition of the mobile phase, chamber saturation time, and analysis wavelength. Silica gel 60 F254 was used as the stationary phase. Stability tests were carried out by analyzing standards and samples at 0, 4, 8, and 24 hours. Results: The best separation that produces symmetrical peaks of herbal medicine was achieved under isocratic conditions using the composition of the mobile phase chloroform : acetone: dichloromethane : acetonitrile : formic acid (6 : 2: 2 : 0,05 : 0.05 v/v/v/v/ v) with a wavelength of 335 nm with a saturation time of 30 minutes. Conclusion: In this study, the optimal conditions for the analysis of luteolin, quercetin, apigenin, and sinensetin. Luteolin, quercetin, apigenin, and sinensetin are unstable during 8 hours of storage. Therefore, standard solutions and samples must be made fresh to maintain stability.